Conservation of Nelapattu Bird Sanctuary - a Review - Kumar, N. V. Nanda; Nagarjuna, A.; Mallikarjuna Rao, P.; Chalapathi Rao, P. V. (Indian Forester, 2012)
Nelapattu Bird Sanctuary (Lat. 13°49' N to 31°51' N; Long. 79°57' E to 59°15' E) is located towards west of East coast of Bay of Bengal and about 20 km west of Pulicat Lake near Sullurpet, Nellore District, Andhra Pradesh. It is one of the biggest pelicanery having approximately 1500 pelicans (Pelecanus philippensis) breeding and roosting. It is also an ideal roosting and breeding for long distant and local migrant birds. Vertical gradient and resource partitioning of migratory birds on Barringtonia tree in Nelapattu Bird Sanctuary is being observed. A gradual and natural domination of open bill storks is observed over a period of time. A review on management of Nelapattu Bird Sanctuary is described for ecological sustainability which include irrigation water management, deweeding and prevention of algal bloom, Prosopis juliflora plantation for roosting of birds, plantation of Subabul trees for procuring nesting material. Feeding of st Krishna river water to last only up to May/June 1st week only to avoid stabilization of new summer birds which might compete for space. A statistical relationship worked out between monsoon rainfall and pelican migration.